Jane Tolmach for Assembly 36th District
This campaign letter from Jane Tolmach to educators during her 1976 Assembly race emphasizes her long-standing support for public education and seeks educators' backing. She argues that inadequate and inequitable school funding—exacerbated by inflation limits and the Serrano v. Priest decision—has created a financial crisis for local districts, forcing program cuts and substandard cost-of-living raises. Tolmach pledges to overhaul public school finance, secure greater financial support for districts, and address funding inequities as the foundation for solving broader educational issues. The letter concludes by inviting educators to endorse her candidacy, allow use of their names in campaign ads, and contribute to her campaign.